Three-dimensional porosity characterization in carbon/glass fiber epoxy hybrid composites - Monticeli, Francisco Maciel [UNESP] (2019)
The main objective of this study is to analyze the effect of the stacking sequence of glass/carbon-reinforced hybrid composites on the impregnation quality and on the formation of voids. This was achieved by creating a three-dimensional (3D) microstructure of the laminates from planar microscopy images. It was demonstrated that the impregnation quality could be improved, and the porosity could be minimized by the appropriate selection of the stacking sequence. The present methodology enables the analysis of the effect of various configurations of hybrid reinforcement on the impregnation behavior, and consequently, the formation of voids. The 3D images enable detailed characterization of porosity through the laminate thickness, including void fraction, the location and morphology of voids. Hybrid composites with glass fibers positioned in the middle proved to have more favorable impregnation, and thus, the uniformity of process-induced voids throughout the composite laminates could be reduced and controlled.